Enhanced Crowbar Protection for Fault Ride through Capability of Wind Generation Systems - V. Mohana Kalyani; J. Preetha Roselyn; C. Nithya; D. Devaraj (Institute of Advanced Engineering and Science, 2016)
Due to increasing demand in power, the integration of renewable sources like wind generation into power system is gaining much importance nowadays. The heavy penetration of wind power into the power system leads to many integration issues mainly due to the intermittent nature of the wind and the desirability for variable speed operation of the generators. As the wind power generation depends on the wind speed, its integration into the grid has noticeable influence on the system stability and becomes an important issue especially when a fault occurs on the grid. The protective disconnection of a large amount of wind power during a fault will be an unacceptable consequence and threatens the power system stability. With the increasing use of wind turbines employing Doubly Fed Induction Generator (DFIG) technology, it becomes a necessity to investigate their behavior during grid faults and support them with fault ride through capability. This paper presents the modeling and simulation of a doubly fed induction generator according to grid code compatibility driven by a wind turbine connected to the grid. This paper analyses the voltage sag due to a three-phase fault in the wind connected grid. A control strategy including a crowbar circuit has been developed in MATLAB/SIMULINK to bypass the rotor over currents during grid fault to enhance the fault ride through capability and to maintain system stability. Simulation results show the effectiveness of the proposed control strategies in DFIG based grid connected wind turbine system.